2019
DOI: 10.3389/fphar.2018.01537
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NMDA-AKT-mTOR Signaling in Rapid Antidepressant-Like Activity of Chaihu-jia-Longgu-Muli-tang on Olfactory Bulbectomized Mice

Abstract: Background: Fast-onset antidepressants are urgently needed. Chaihu-jia-Longgu-Muli-tang (CLM), a classic Chinese herbal medicine, has been used for antidepressant treatment with long history. Olfactory bulbectomization (OB) model is validated for identification of rapid antidepressant efficacy. Here we used OB model for investigating the rapid onset activity of CLM in mice, and also tested the involvement of prefrontal Akt-mTOR and associated AMPA/NMDA receptors as well as hippocampal BDNF in the rapid antidep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The individual herbs composing CLMD are Bupleuri radix, Fossilia ossis mastoid, Scutellariae radix, Zingiberis rhizoma, Ginseng radix, Cinnamomi cortex, Hoelen, Pinelliae tuber, Radix et Rhizoma Rhei, Osttreae testa, Zizyphi fructus, all of which are recorded in the Chinese Pharmacopoeia (Version 2010). [22] According to CHM theory, this prescription is reported to clear heat and eliminate dampness, and tranquilize with heavy prescription. The details of CLMD are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The individual herbs composing CLMD are Bupleuri radix, Fossilia ossis mastoid, Scutellariae radix, Zingiberis rhizoma, Ginseng radix, Cinnamomi cortex, Hoelen, Pinelliae tuber, Radix et Rhizoma Rhei, Osttreae testa, Zizyphi fructus, all of which are recorded in the Chinese Pharmacopoeia (Version 2010). [22] According to CHM theory, this prescription is reported to clear heat and eliminate dampness, and tranquilize with heavy prescription. The details of CLMD are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…A dose of ethanol extracts from Yueju pill (3 g/kg) rapidly attenuated depressive-like behaviors, increased hippocampal BDNF expression, activated prefrontal Akt-mTOR signaling, and downregulated NR1 expression within days (Xue et al, 2013;Tang et al, 2015;Xia et al, 2016). Chaihu-jia-Longgu-Muli-tang (a single dose of 2.1 g/kg) has also been shown to produce a rapid antidepressant-like activity in olfactory bulbectomization mice through activation of Akt-mTOR signaling and normalization of AMPA receptor/NMDA receptor ratio in PFC (Wang et al, 2019b). In addition, these formulas have previously been shown to produce antidepressant actions through monoaminergic systems as well as the HPA axis in chronic animal models (Mizoguchi et al, 2003;Wang et al, 2013).…”
Section: Glutamate Transmissionmentioning
confidence: 99%
“…Previous studies have reported the downregulation of the mTOR signaling pathway in postmortem human brain samples from subjects with MDD [39], as well as in PFC, hippocampus, and amygdala of several animal models of depression including the olfactory bulbectomy, chronic unpredictable stress (CUS), and chronic corticosterone exposure [40][41][42][43][44]. In order to examine the role of the mTOR pathway in the IL cortex as a neurobiological substrate in MDD, we evaluated in this study the effects of the mTOR knockdown in mouse IL cortex on the anxious-and depressive-like behavior, the expression of synaptic plasticity markers as the brain-derived neurotrophic factor (BDNF) using in situ hybridization, and used in vivo microdialysis to explore the evoked adaptive changes in cortico-subcortical circuits leading to the emergence of a depressive-like phenotype.…”
Section: Introductionmentioning
confidence: 99%